The nature and functions of dreaming - Hartmann, Ernest, 1934- (New York ; Oxford : Oxford University Press, 2010)
This work presents a comprehensive theory of dreaming based on many years of psychological and biological research by Ernest Hartmann and others.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Dreams; Dream interpretation